Seahorse Acoustic Reflection on Active and Passive Moving Condition : A Prelyminary Observation in Watertank - Dony Apdillah; Indra Jaya; Henry Munandar Manik; Totok Hestirianoto; Try Febrianto (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2018)
Identification and estimation of seahorse population in the marine environment are difficult to obtain. Nowadays, the observations use visual techniques, biologic and statistics. Bio-statistics approach has some limitations, such as times consuming and low accuracy. An approach was required to provide more accurate information, comprehensive, and based on telemetry (underwater acoustic). Acoustic reflection is an important information to observe underwater objects that can be used for stock assessment and behavioral studies. This research is a preliminary observation and measurement of seahorse Target Strength (TS). The results show that there are differences in TS value of seahorse at the active and passive moving condition. The fluctuations of TS values in active conditions are higher than those in passive conditions. This study has also found that the average TS value of seahorse in active moving conditions is -54.49 dB (± 3 dB). It is greater than the mean TS value in passive moving conditions -59.64 dB (± 3 dB). The approach of immobile fish (the passive moving condition) on the seahorse is better to increase the correlation value between TS to size. The relationship between TS and the size of the seahorse are discussed in the results of this study